The Casimir effect - Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The quantization of the electromagnetic field gives rise to quantum fluctuations which in turn produce a force on macroscopic boundaries. This phenomenon is called the Casimir effect. Method: The second quantization of the electromagnetic field is employed. The Zeta function regularization technique has been applied. Results: Because of the electromagnetic field quantization, a force on macroscopic boundaries is observed. Conclusions: Vacuum fluctuations due to quantum effects give macro- scopic results.